Segmentação do ventrículo esquerdo em ecocardiogramas usando contornos ativos (snake) - Bouhours, Antoine (2006)
The cardiac illnesses represent the most of death cause in developed countries and one of the commonest in developing countries, which is the case of Brazil. In order to detect them, different existing methods can be applied. Among them, the ECG (electrocardiogram), methods developed from nuclear medicine and echocardiogram of effort (ECE). This last one is preferred due to its low cost, in comparison with the nuclear medicine and its non-invasive ability. For these reasons, ECE is used to diagnostic the isquemia (muscular elasticity loss). But the diagnostic is done by a specialist through the visualization of a video, and is consequently subjective. This master degree dissertation describes a segmentation method of the left ventricle in ecocardiograms, using the active contours model (snake), in order to the ECE becomes more objective, allowing an automatic measure of left ventricle and consequently the detection of isquemia. Denoising techniques are implemented because this kind of image is corrupted by the speckle noise, what is harmful for analises. Wavelet-based technics are developed and four algorithms are compared in measuring the time of execution and the resulting signal to noise ratio. From the resulting denoised images, a technique for left ventricle border detection is developed using the snake methods. Partial results show an effective result for the detection of intern myocardium borders which represent the left ventricle.